Variability in humpback whale songs reveals how individuals can be distinctive when sharing a complex vocal display - Lamoni, Luca Ubaldo; Garland, Ellen Clare; Allen, Jenny; Coxon, Jennifer; Noad, Michael J; Rendell, Luke Edward (The Journal of the Acoustical Society of America, 2023)
Funding: L.L. was supported by a Leverhulme Trust Grant to L.R. (among other recipients; grant reference RPG-2013-367). L.R. was supported by the MASTS pooling initiative (The Marine Alliance for Science and Technology for Scotland) and their support is gratefully acknowledged. MASTS is funded by the Scottish Funding Council (grant reference HR09011) and contributing institutions. ECG was funded by a Royal Society Newton International Fellowship and a Royal Society University Research Fellowship. J.A.A. was funded by an Australian Government Research Training Programme Scholarship and the Australian American Association University of Queensland Fellowship. The HARC project was funded by the US Office of Naval Research, the Australian Defence Science and Technology Organisation, and the Australian Marine Mammal Centre. Individually distinctive acoustic signals in animal vocal communication are taxonomically widespread, however, the investigation of these signal types in marine mammals has focused only on a few species. Humpback whale songs are a stereotyped, hierarchically structured vocal display performed by males, and hence thought to be sexually selected. Within a population, whales conform to a common version of the song despite the song constantly evolving. While humpback songs have been studied extensively at the population level, individual level variation has been rarely described, with inconclusive results. Here we quantified inter- and intra-individual variability at different levels in the song hierarchy using songs from 25 singers across two song types from the eastern Australian population song of 2002 (12 singers), and the revolutionary song introduced in 2003 (13 singers). Inter- individual variability was found heterogeneously across all hierarchical levels of the song structure. In addition, distinct and individually specific patterns of song production were consistently recorded across song levels, with clear structural differences between the two song types. These results suggest that within ...